A perspective on natural potential compounds against SARS COV-2: The case of Bioflavonoids against 3C-like proteinase (3Cl-pro) and the role of Benzylisoquinoline Alkaloids, (BIAs), against SARS-CoV-2 Spike - Ferrari, I. V.; Mario, M. Di; Narducci, R.; Bracco, A.; Patrizio, P. (International Journal of Scientific Research in Computer Science and Engineering, 2021)
In this paper, we have investigated two different typology natural compounds, by rapid molecular docking approach, using Autodock Vina with Pyrx Software. The main idea was focused to evaluated different bioflavonoids, against SARS COV-2 3C-like proteinase, (3Cl-pro). From our results of Molecular Docking, in the Ligand Binding Site pocket, we have proposed six active flavonoids, equipped with high Binding Energy Score (kcal/mol), about -10 kcal/mol-1. They are Sequoiaflavone, Bilobetin, Cupressuflavone, Amentoflavone, Ginkgetin, and Theaflavin, respectively, potentially useful against 3Cl-pro. Moreover, we have also performed another category, equipped with anticancer properties. They are Benzylisoquinoline Alkaloids ( BIAs), in which they are potentially active against SPIKE-SARS-CoV-2 RBD, demonstrating that BIAs exhibited significantly higher binding Energy values of ca -10; -11 kcal mol-1, in the Receptor Binding Domain of Spike Glycoprotein.